2016
DOI: 10.11616/basbed.vi.455852
|View full text |Cite
|
Sign up to set email alerts
|

Pedogoji̇k Formasyon Eği̇ti̇mi̇ Alan Öğrenci̇leri̇n Uzaktan Eği̇ti̇me Yöneli̇k Tutumlari

Abstract: Bu araştırmanın amacı, Pedagojik Formasyon eğitimi alan öğrencilerin uzaktan eğitime yönelik tutum düzeylerini belirlemektir. Araştırmanın çalışma evrenini, 2014-2015 öğretim yılında Abant İzzet Baysal Üniversitesi Eğitim Fakültesinde Formasyon eğitimi öğrencilerİ oluşturmaktadır. Araştırmanın çalışma evreni toplam 1512 öğrencidir. Çalışma evreninden örneklem alma yoluna gidilmiştir. Örneklemini ise, çalışma evreninden seçkisiz olarak seçilen 653 formasyon eğitimi alan öğrenci oluşturmaktadır. Araştırmada veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 2 publications
(4 reference statements)
0
7
0
3
Order By: Relevance
“…It was established that the attitude of the lecturers towards distance education was high in the faculty of social sciences and low in the faculty of engineering sciences. Similar to this study, a crucial relationship was determined between departments and distance education (Ugras, Altunbas, Ay, & Cil, 2012;Gündüz, 2013;Yılmaz & Güven, 2015;Yıldız, 2016). In the study conducted by Aras (2019) with academic staff, it was observed that they stated that distance education will provide benefits in theoretical courses and disadvantages will arise in applied courses.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…It was established that the attitude of the lecturers towards distance education was high in the faculty of social sciences and low in the faculty of engineering sciences. Similar to this study, a crucial relationship was determined between departments and distance education (Ugras, Altunbas, Ay, & Cil, 2012;Gündüz, 2013;Yılmaz & Güven, 2015;Yıldız, 2016). In the study conducted by Aras (2019) with academic staff, it was observed that they stated that distance education will provide benefits in theoretical courses and disadvantages will arise in applied courses.…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…Studies in the literature show that there is an important relationship between professional seniority and distance education. In parallel with the study conducted in some studies, the level of attitude towards distance education decreases as the professional seniority increases (Ağır, 2007;Akgül, 2021;Ateş & Altun, 2008;Birişçi, 2013;Gök, 2011;Horzum et al, 2012;Kışla, 2005;Şimşek et al, 2010;Yermeydan Uğur, 2017;Yıldız, 2016). The distance education experience (Al-Balas et al, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, according to the study conducted by Çiftçioğlu (2022) preservice preschool teachers have a moderate level attitude towards distance education and there is a significant positive relationship between the digital literacy abilities of students with their attitudes. There are other studies in the literature which concluded that students are negative or undecided about distance education (Ural, 2007;Yıldız, 2016). On the other hand, Yenilmez et al (2017) revealed that attitudes of pre-service teachers from different departments towards distance education are positive.…”
Section: Introductionmentioning
confidence: 92%
“…Çağın gerektirdiği bilimsel ve teknolojik gelişmeler, insanların değişen ihtiyaçları doğrultusunda yeni öğrenme yöntemleri ve ortamlarına ihtiyaç doğurmuştur. 21. yüzyıl küresel bilgi toplumunda gelişen teknoloji ile meydana gelen çok büyük değişim ve gelişmeler, yeni öğrenme ortamlarından birisi olan uzaktan eğitim kavramını ortaya çıkarmıştır (Yıldız, 2016). Holmberg (1995), uzaktan eğitimi, planlama, rehberlik ve öğretim boyutu bulunan, öğrenci ve öğretmenlerin ders yapılan ortamda bulunma zorunluluğu olmayan ve öğrencinin öğretmen denetiminde olmadığı bir yöntem olarak tanımlamıştır.…”
Section: Introductionunclassified